Upaya Meningkatkan Kualitas Sumber Daya Manusia Desa Cibaliung Melalui KUM-ITT Universitas Trisakti di Pandeglang Banten - Dwiyandana, Dani (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Cibaliung village has been chosed as one of the pioneer of ‘Kuliah Usaha Mandiri’ – Ilmu Teknologi Terapan (KUM-ITT) Trisakti University. The reason is because this village has an economic potential, that is the transit track to tourism object from Labuan to Ujung Kulon and Umang island. In addition, Cibaliung village has a variety of potential natural resources that could be evolved to support the needs the progressing of coast tourism object along Umang Island and Ujung Kulon. However, the aspect of human resources potential has several weakness, it is caused by limited technology and knowledge in managing and developing the natural resources which supports for coastal tourism. The results of field survey show that the limitations of technology and knowledge in Cibaliung village covers areas including: 1). Health, 2). Law, 3). Economy, 4). Physical and environment, 5). Appropriate technology, 6). Social and cultural. Community Service activities include ‘KUM-ITT’ activity to train students of Trisakti University in order to perceive the various matters in society and determine the solution, as well as efforts to improve the quality of human resources in Cibaliung village, Pandeglang. The ‘KUM-ITT’ implements survey methods, extension, and demonstration in the form of a pilot. The results show that the activities of human resources improvement in Cibaliung village was not arduous to apply as motivation of society and potential environment can still be managed for further explored. The improvement can be seen through economy society through domestic industry, marketing, and the area of health especially in public awareness in maintaining healthy families and environments